PENGARUH FASILITAS SEKOLAH JARAK KUALITAS PENGAJARAN DUKUNGAN ORANG TUA DAN CITRA SEKOLAH TERHADAP MINAT SISWA BERSEKOLAH DI SMK SWASTASTUDI DI SMK NU KERTASEMAYA KABUPATEN INDRAMAYU - Ertini; Mulyadi, Edi; Hardian, Dafyar Eliadi (Perspektif : Jurnal Ilmu Administrasi, 2025)
The decline in the number of students in private vocational high schools is a serious challenge, particularly in rural areas. This study aims to analyze the factors influencing students' interest in choosing to attend SMK NU Kertasemaya in Indramayu Regency. The research focused on five main variables: school facilities, distance, teaching quality, parental support, and school image. The research method used was a quantitative approach with a survey technique. A sample of 73 students was selected using a purposive sampling technique. Data were collected through questionnaires and then analyzed using multiple linear regression to test the partial and simultaneous effects of each variable on student interest. The results showed that all independent variables significantly influenced student interest, both partially and simultaneously. Adequate school facilities, accessible distance, good teaching quality, high parental support, and a positive school image were proven to encourage increased student interest. Thus, a school's success in attracting prospective students depends on the synergy of these various factors. This research provides a practical contribution to school administrators in formulating data-driven promotion and quality development strategies. Furthermore, the results can also be used as considerations in education policymaking at the local level. Keywords: Student Interest, School Facilities, Teaching Quality, Travel Distance, Parental Support, School Image.